Identification of a phosphoenolpyruvate:fructose 1-phosphotransferase system in Azospirillum brasilense. - Gupta, K D (1984)
An inducible phosphoenolpyruvate:fructose phosphotransferase system has been detected in Azospirillum brasilense, which requires a minimum of two components of the crude extracts for activity: (i) a soluble fraction (enzyme I) and (ii) a membrane fraction (enzyme II). The uninduced cells neither show any uptake of fructose nor express activity of either of these two enzyme fractions. C-1 of fructose is the site of phosphorylation. This phosphotransferase system does not accept glucose as a substrate for phosphorylation.